2020
DOI: 10.3390/horticulturae6030050
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit Production in Open Hydroponics System

Abstract: Conventionally managed citrus orchards can be modified to incorporate advanced horticultural practices such as higher plant density and efficient water and fertilizer application known as open hydroponics system (OHS) to increase productivity under Huanglongbing (HLB) endemic conditions. A field study was conducted from 2013 to 2018 to evaluate the effect of an OHS on “Ray Ruby” grapefruit (RR) production under HLB-endemic conditions. We tested a combination of different rootstocks [Sour orange (RR/SO) and US-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Though it has not been investigated in lime production yet, the OHS has been reported to be highly suitable for citrus production. Regarding the horticulture practice, the OHS increased the citrus yield by over 20% that has been widely reported (Morgan et al, 2009;Prazeres et al, 2017;Ferrarezi et al, 2020). In particular, five-year observation of using the OHS in the citrus orchards infected by Huanglongbing (HLB) disease showed that the system is suitable for application with higher tree density even under the common disease condition (Ferrarezi et al, 2020).…”
Section: Mechanization For Small and Medium Farmsmentioning
confidence: 87%
See 1 more Smart Citation
“…Though it has not been investigated in lime production yet, the OHS has been reported to be highly suitable for citrus production. Regarding the horticulture practice, the OHS increased the citrus yield by over 20% that has been widely reported (Morgan et al, 2009;Prazeres et al, 2017;Ferrarezi et al, 2020). In particular, five-year observation of using the OHS in the citrus orchards infected by Huanglongbing (HLB) disease showed that the system is suitable for application with higher tree density even under the common disease condition (Ferrarezi et al, 2020).…”
Section: Mechanization For Small and Medium Farmsmentioning
confidence: 87%
“…Regarding the horticulture practice, the OHS increased the citrus yield by over 20% that has been widely reported (Morgan et al, 2009;Prazeres et al, 2017;Ferrarezi et al, 2020). In particular, five-year observation of using the OHS in the citrus orchards infected by Huanglongbing (HLB) disease showed that the system is suitable for application with higher tree density even under the common disease condition (Ferrarezi et al, 2020). The OHS system has been also documented to be more economical for capital investment.…”
Section: Mechanization For Small and Medium Farmsmentioning
confidence: 87%
“…As it is generally difficult to control and measure the absorption of mineral nutrients under soil cultivation, hydroponics systems are widely used [15][16][17][18][19][20][21][22][23][24]. These systems allow easy nutrient solution management and optimal supply of mineral elements in soluble form [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%